Matrix Metalloproteinase-9 (MMP-9) induced disruption of intestinal epithelial tight junction barrier is mediated by NF-κB activation. - Rana Al-Sadi; Jessica Engers; Mohammad Haque; Steven King; Deemah Al-Omari; Thomas Y Ma (PLoS ONE, 2021)
Background Matrix Metalloproteinase-9 (MMP-9) has been shown to play a key role in mediating inflammation and tissue damage in inflammatory bowel disease (IBD). In patients with IBD, the intestinal tight junction (TJ) barrier is compromised as characterized by an increase in intestinal permeability. MMP-9 is elevated in intestinal tissue, serum and stool of patients with IBD. Previous studies from our laboratory showed that MMP-9 causes an increase in intestinal epithelial TJ permeability and that the MMP-9 induced increase in intestinal permeability is an important pathogenic factor contributing to the development of intestinal inflammation in IBD. However, the intracellular mechanisms that mediate the MMP-9 modulation of intestinal barrier function remain unclear. Aims The main aim of this study was to further elucidate the molecular mechanisms involved in MMP-9 induced increase in intestinal epithelial TJ permeability using Caco-2 monolayers as an in-vitro model system. Results MMP-9 induced increase in Caco-2 TJ permeability was associated with activation and cytoplasmic-to-nuclear translocation of NF-κB p65. Knocking-down NF-κB p65 by siRNA transfection prevented the MMP-9 induced expression of the NF-κB target gene IL-8, myosin light chain kinase (MLCK) protein expression, and subsequently prevented the increase in Caco-2 TJ permeability. In addition, the effect of MMP-9 on Caco-2 intestinal epithelial TJ barrier function was not mediated by apoptosis or necrosis. Conclusion Our data show that the MMP-9 induced disruption of Caco-2 intestinal epithelial TJ barrier function is regulated by NF-κB pathway activation of MLCK.